Comparison of the Effect of Different Physical Therapy Methods on Lumbopelvic Stability among People with Low Back Pain - Justė Knatauskaitė (Lithuanian Sports University, 2020)
Research background. The majority of persons suffer from low back pain and prevalence of it seeks about 84%. Chronic low back pain is the second cause for people to go to their general practitioner. Many studies are done about treatment of chronic low back pain; however, complaints about back pain are increasing. Therefore we are going to find out which of the three our applied methods is the best for treating low back pain. The aim of the study was to compare the impact of different physical therapy methods on lumbopelvic stability control among people with chronic low back pain. Methods. 30 people with low back pain were participating in this study. Following factors were estimated before and after eight physical therapy sessions: intensity of pain by using the scale of numbers (SAS); lumbopelvic stability control by using "Stabilizer" pressure biofeedback unit; functional motions performance capacity by doing functional tasks. Results. Statistically significant changes were not found after the evaluation of lumbopelvic stability control under the method of Redcord sliding suspension system, elastic resistance and body weight exercises before and after physical therapy sessions. Statistically significant correlations were found between lumbopelvic stability control and pain intensity in those groups where people were training under the methods of elastic resistance and body weight exercises (p < 0.05). Statistically significant correlations were found between lumbopelvic stability control and functional motions performance capacity in those groups where people were training under the methods of Redcord sliding suspension system and body weight exercises (p < 0.05). Conclusion: statistically significant change was not found between three intervention groups after physical therapy; therefore neither of three methods applied in this study was better than the others. Keywords: chronic low back pain, lumbopelvic stability control, functional movement performance capacity, physical therapy.